The Effectiveness of Pulmonary Rehabilitation on Pulmonary Function among Adults Patients of COVID-19 Survivors: A Systematic Review - Hasanudin Hasanudin; Tintin Sukartini; Makhfudli Makhfudli; Alfian Nur Rosyid; Handira Nadhifatul Aini; Natalia Christin Tiara Revita (Jurnal Respirasi, 2022)
Introduction: Corona Virus Infection Disease (COVID-19) refers to the infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Most of COVID-19 survivors have residual symptoms after being discharged from the hospital, it then leads to the decreased lung function and quality of life (QoL). Pulmonary rehabilitation is essential because it can reduce the impact of these sequelae. This study aimed to determine the effectiveness of pulmonary rehabilitation in improving lung function among adult patients of COVID-19 survivors.Methods: This study was conducted using 5 databases, namely: CINAHL, PubMed, SAGE, Science Direct, and Scopus from 1 April 2020 to 30 September 2021. The combination of keywords used was: "Pulmonary Rehabilitation", “Pulmonary Function", and "Post-COVID-19". In assessing the bias and methodological quality of the articles obtained, this study used the Joanna Briggs Institute (JBI) critical appraisal checklist tools.Results: From 678 articles, 11 research articles met the criteria. Pulmonary rehabilitation performed in post-COVID-19 patients included the provision of aerobic exercise, breathing exercises, strength training, balance exercises, relaxation, occupational therapy, psychological support, and nutrition consultation. Lung rehabilitation mainly was performed two sessions a week for 3-8 weeks with different proportions for each patient according to clinical conditions and  ability limits. Spirometry and the 6-minute walk test (6MWT) revealed that patients who completed the pulmonary rehabilitation program experienced improvements in their lung function.Conclusion: Comprehensive pulmonary rehabilitation programs under supervision and psychotherapists are the right choice in improving lung function among COVID-19 survivor adult patients.